Repeatability of Manual Measurement of Foveal Avascular Zone Area in Optical Coherence Tomography Angiography Images in High Myopia - Lee, Jong Ha; Lee, Min Woo; Baek, Seung Kook; Lee, Young Hoon (Korean journal of ophthalmology, 2020)
To analyze the repeatability of manual measurement of foveal avascular zone (FAZ) area in an optical coherence tomography angiography (OCTA) image in high myopia. This study comprised patients with high myopia and controls. Two consecutive FAZ areas of the superficial and deep capillary plexus were obtained using OCTA. The intraclass correlation coefficient (ICC) and coefficient of variation (CV) were assessed, and univariate and multivariate generalized linear mixed models were conducted to identify factors related to repeatability. Thirty eyes with high myopia and 34 eyes of healthy subjects were included in the study. The mean age in high myopia and control subjects was 55.5 and 60.8 years, respectively, the mean spherical equivalent was -9.98 and -0.55 diopters, and the mean axial length was 28.0 and 23.9 mm. The ICCs of FAZ area of the superficial capillary plexus (SCP) were 0.891 and 0.919, while the CVs were 8.8% and 8.5%. In measurement of the deep capillary plexus, the ICCs were 0.788 and 0.907, while the CVs were 11.2% and 11.0%, which were acceptable but exhibited lower repeatability than those of SCP. Multivariate analyses showed that older age ( = 0.030) and greater axial length ( = 0.005) were significantly associated with lower repeatability of SCP FAZ area measurements. In addition, greater axial length ( = 0.044) was a significant factor for lower repeatability of deep capillary plexus FAZ area measurements. Manual measurement of FAZ area using OCTA exhibited relatively good repeatability for high myopia. Age and axial length affected repeatability and should be considered when analyzing FAZ areas in high myopia patients.